Single cell transcriptome analysis identified a unique neutrophil type associated with Alzheimer’s disease - Zhang, Xiaolin; He, Guiqin; Hu, Yixuan; Liu, Boren; Xu, Yuliang; Li, Xia; Lv, Xinyou; Li, Jin (Immunity & ageing, 2024)
Neutrophils play an essential role in Alzheimer's disease (AD) pathology. However, the extent of their heterogeneity remains poorly explored, particularly in the context of developing novel therapies targeting these cells. We investigate the population structure of neutrophils purified from peripheral blood samples of AD mice. Utilizing single cell RNA sequencing, we comprehensively map neutrophil populations into six distinct clusters and find that the Neu-5 subset is specially enriched in AD mice. This subset exhibits fewer specific granules and a lower mature score. Gene ontology (GO) analysis reveals that genes involved in cytokine-mediated signaling are downregulated in the Neu-5 cluster. Furthermore, we identify the Ccrl2 gene is specifically upregulated in this subgroup, which is confirmed by flow cytometry in AD mice. Finally, immunohistochemical staining indicates that CCRL2 protein is increased in the brains of AD mice. We identify a unique CCRL2 positive neutrophil cluster, that is specifically enriched in the peripheral blood of AD mice.